Practice of pharmaceutical care by community pharmacists in response to self-medication request for a cough: a simulated client study - Pengyeow Loh; Jason W. Lee; Mahmathi Karuppannan; Siew Siang Chua (BMC, 2023)
Abstract Background Community pharmacy practice worldwide has been shifting from product-focused to patient-oriented. However, due to the absence of separation between prescribing and dispensing in Malaysia, community pharmacists may have limited roles in the provision of pharmaceutical care to patients with chronic diseases. Therefore, the main functions of community pharmacists in Malaysia are related to self-medication requests for minor ailments and the supply of non-prescription medications. The objective of this study was to determine the practice of pharmaceutical care by community pharmacists within the Klang Valley, Malaysia in response to self-medication requests for a cough. Methods This study utilised a simulated client method. A research assistant, acting as a simulated client, visited community pharmacies in the Klang Valley, Malaysia to consult the pharmacists on the treatment of a cough experienced by his father. Upon leaving the pharmacy premise, the simulated client entered the pharmacist's responses in a data collection form which was structured based on pharmacy mnemonics for the response to symptoms, OBRA'90 on counselling elements, the five practice principles of pharmaceutical care by the American Pharmacists Association and literature review. Visits to the community pharmacies were conducted from September to October 2018. Results The simulated client visited a total of 100 community pharmacies. None of these community pharmacists practised adequate patients' data collection, with only a low proportion who practised all the components studied under medication information evaluation (13%), formulating a drug therapy plan (15%) and monitoring and modifying the plan (3%). Of the 100 community pharmacists, 98 recommended treatment but none of them provided all the counselling elements studied in implementing the drug therapy plan. Conclusion The present study showed that community pharmacists within the Klang Valley, Malaysia were not providing adequate pharmaceutical care services to patients seeking self-medication for a cough. Such practice may compromise patient safety if inappropriate medicines or advice are given.